Strengthening higher education for a successful workforce - Abd Rahman, Shukran (IIUM Press, 2009)
Introduction: The emergence of high-tech era and information-based era have outperformed the glory of industrial era. Dychtwald, Erickson and Morison, (2006) have identified this era as tech boom era which is characterised by the epoch of globalisation, giving rise to the emergence of global demographics at workplaces. Workforce too need to be equipped with more knowledge and skills for only competent workforce can meet various job challenges, demands, and opportunities. The current world of work is characterised by rapid and uncertain economic changes coupled with technological advancement, requiring the need to train and retrain workforce in order to equip them with the latest changes of technologies, contemporary skills requirements and other up to date competencies. This is essential to make them relevant with the current and even the future world of work.